Long-term safety of sarilumab in rheumatoid arthritis: an integrated analysis with up to 7 years' follow-up. (15th July 2019) - Fleischmann, Roy; Genovese, Mark C; Lin, Yong; St John, Gregory; van der Heijde, Désirée; Wang, Sheldon; Gomez-Reino, Juan Jose; Maldonado-Cocco, Jose Antonio; Stanislav, Marina; Kivitz, Alan J; Burmester, Gerd R
Abstract: Objective: Sarilumab is a human monoclonal antibody that blocks IL-6 from binding to membrane-bound and soluble IL-6 receptor-α. We assessed the long-term safety of sarilumab in patients from eight clinical trials and their open-label extensions. Methods: Data were pooled from patients with rheumatoid arthritis who received at least one dose of sarilumab in combination with conventional synthetic disease-modifying antirheumatic drugs (csDMARDs; combination group) or as monotherapy (monotherapy group). Treatment-emergent adverse events (AEs) and AEs and laboratory values of special interest were assessed. Results: 2887 patients received sarilumab in combination with csDMARDs and 471 patients received sarilumab monotherapy, with mean exposure of 2.8 years and 1.7 years, maximum exposure 7.3 and 3.5 years, and cumulative AE observation period of 8188 and 812 patient-years, respectively. Incidence rates per 100 patient-years in the combination and monotherapy groups, respectively, were 9.4 and 6.7 for serious AEs, 3.7 and 1.0 for serious infections, 0.6 and 0.5 for herpes zoster (no cases were disseminated), 0.1 and 0 for gastrointestinal perforations, 0.5 and 0.2 for major adverse cardiovascular events, and 0.7 and 0.6 for malignancy. Absolute neutrophil counts <1000 cells/mm 3 were recorded in 13% and 15% of patients, respectively. Neutropenia was not associated with increased risk of infection or serious infection. Analysis by 6-month interval showed no signal for increased rate of any AE over time. Conclusion: The long-term safety profile of sarilumab, either in combination with csDMARDs or as monotherapy, remained stable and consistent with the anticipated profile of a molecule that inhibits IL6 signalling.